The working conditions of screenwriters in Turkish television series sector: neoliberalism, global rivalry and labour exploitation - Sevim, Seçkin (My University, 2016)
Television series screenwriting has become a popular job since commercial television broadcasting started and Turkish television series sector revived in Turkey. The commercial success of Turkish television series in both internal and foreign markets has brought labour exploitation to the agenda experienced by screenwriters. The Society of Script and Dialog Writer Cinematographic Work Owners (SENARİSTBİR) and The Screenwriters Association (SENDER) could not yet take effective steps to stop labour exploitation in the sector. There is a large literature regarding the problems of screenwriters working in television series sector in developed western countries. In spite of that there is a serious gap in this field in Turkey. This study aims to make academies, non-governmental organisations and independent researchers show more interest to this issue. This study carried out as quantitative analysis approach was limited to the screenwriters working in Turkish television series sector. Semi-structured interviews were held with the screenwriters selected as a purposeful sampling. Interviews were analyzed using the categories such as “uncertainty”, “employment insecurity”, “copyright”, “long working hours”, “creativity” and “social rights”. The literature regarding “Neolibelarism”, “global rivalry” and “labour exploitation” were analyzed by considering semi-structured interviews data. As a result, by presenting the extent of the labour exploitation in Turkish television series sector, the idea of solidarity will be stronger in the sector; and producers and publishers will remember their responsibility about the issue.
Keywords: Turkish Television Series Sector, Screenwriter, Neoliberalism, Global Rivalry, Labour Exploitation